gamma-Aminobutyric acid is an inhibitory neurotransmitter restricting the release of luteinizing hormone-releasing hormone before the onset of puberty. - Mitsushima, D (1994)
To test the hypothesis that the pubertal increase in luteinizing hormone-releasing hormone (LHRH) release is withheld by a dominant inhibitory neuronal system, the role of gamma-aminobutyric acid (GABA), a known inhibitory neurotransmitter, in the control of LHRH release was examined in conscious female monkeys at the prepubertal and pubertal stages using a push-pull perfusion method. GABA, bicuculline (a GABAA receptor blocker), and 2-hydroxysaclofen (a GABAB receptor blocker) were directly infused into the stalk-median eminence while perfusates were collected for LHRH determination. Bicuculline, but not saclofen, induced a large and prompt increase in LHRH release in prepubertal monkeys, whereas it stimulated LHRH release slightly in pubertal monkeys. In contrast, GABA suppressed LHRH release in pubertal, but not prepubertal, monkeys. These differential effects of GABA and the GABA antagonist on LHRH release in the two developmental stages were due to an age factor rather than to the steroid hormonal background. Moreover, GABA release in the stalk-median eminence of prepubertal monkeys was much higher than that in pubertal monkeys. Thus, the results suggest that in the prepubertal period there is a powerful GABA inhibition of the LHRH neurosecretory system: infusions of GABAA, but not GABAB, antagonists stimulate LHRH release by removal of the endogenous GABA inhibition, whereas exogenous GABA is ineffective because of high endogenous GABA levels. The decrease of this tonic inhibition may be a key factor for the onset of puberty in non-human primates.